Flue gas desulfurization calcium-based sorbent and method of making same
Patent Information
- Application Number
- CN202611433041.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
这些产物层会覆盖并堵塞脱硫剂基体表面的孔隙网络,阻止SO2气体向内部扩散,导致脱硫剂内部大量的钙基活性组分无法有效参与脱硫反应,造成钙利用率显著偏低,不仅降低了脱硫效率,也造成了脱硫剂资源的严重浪费
造孔剂由膨胀珍珠岩和尿素复配而成。膨胀珍珠岩为经过加热膨胀形成的多孔矿物材料,内部呈蜂窝状多孔结构,在吸附剂成型过程中可作为刚性大孔骨架,预先在吸附剂内部构筑并预留出大孔结构,为气体扩散提供通道。尿素在煅烧阶段受热分解后释放气体,在吸附剂基体内部形成大量相互连通的介孔结构。膨胀珍珠岩提供的刚性大孔与尿素分解产生的连通介孔相互协同,共同构建出具有梯度分布特征的多级孔道体系,有利于烟气中的SO2气体快速扩散至吸附剂内部。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorbent technology, and in particular to a calcium-based adsorbent for flue gas desulfurization and its preparation method. Background Technology
[0002] Sulfur dioxide is one of the major air pollutants, and its emissions are causing increasingly serious environmental problems such as acid rain and smog. In order to achieve efficient removal of sulfur dioxide from flue gas and control emissions from coal-fired industrial sources, various flue gas desulfurization technologies have emerged and continue to develop.
[0003] Calcium-based desulfurizers have become one of the most widely used absorbents in the field of industrial flue gas desulfurization due to their wide availability of raw materials, low cost, high desulfurization efficiency, and mature technology. Calcium-based desulfurizers dominate wet, semi-dry, and dry flue gas desulfurization processes, and have been widely applied in stationary source flue gas treatment, particularly in large and medium-sized coal-fired power plants, steel sintering machines, waste incineration plants, and chemical kilns.
[0004] Currently, the main active components of calcium-based adsorbents are Ca(OH)2 or CaO, which react with SO2 during the desulfurization process to generate CaSO3 or CaSO4 product layers. These product layers cover and block the porous network on the surface of the desulfurizer matrix, preventing SO2 gas from diffusing into the interior. As a result, a large amount of calcium-based active components inside the desulfurizer cannot effectively participate in the desulfurization reaction, leading to a significantly low calcium utilization rate. This not only reduces desulfurization efficiency but also causes a serious waste of desulfurizer resources. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a calcium-based adsorbent for flue gas desulfurization and its preparation method, aiming to prepare a calcium-based adsorbent with a multi-level porous structure and high calcium utilization rate.
[0006] To solve the above technical problems, the flue gas desulfurization calcium-based adsorbent comprises the following components in parts by weight: The mixture comprises 45-55 parts calcium hydroxide, 10-15 parts composite clay mineral, 6-8 parts binder, 6-10 parts auxiliary agent, 3-10 parts titanium dioxide, 3-8 parts zirconium oxide, 3-6 parts diatomaceous earth, 4-10 parts fly ash, 2-5 parts anhydrous sodium sulfate, 2-6 parts catalyst, and 1-3 parts citric acid; the composite clay mineral is composed of hydrotalcite and palygorskite in a mass ratio of 1-3:2-4.
[0007] Preferably, the adhesive is composed of 3.5 to 4.5 parts silica sol and 2.5 to 3.5 parts aluminum phosphate.
[0008] Preferably, the catalyst is one or more of ferric sulfate, cerium oxide, magnesium oxide, and manganese sulfate.
[0009] Preferably, the auxiliary agent consists of 1 to 3 parts surfactant, 3 to 5 parts pore-forming agent and 1 to 2 parts dispersant.
[0010] Preferably, the pore-forming agent is a compound of expanded perlite and urea in a mass ratio of 3-5:1-3.
[0011] Preferably, the surfactant is one or more of polyethylene glycol, sodium lignosulfonate, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide.
[0012] Preferably, the dispersant is one or more of sodium hexametaphosphate, sodium pyrophosphate, and sodium polyacrylate.
[0013] The preparation method of the above-mentioned calcium-based adsorbent for flue gas desulfurization includes the following steps: S1. Weigh each raw material according to the formula proportions, add 20-35% water of the total mass of the raw materials, stir and mix evenly to obtain mud; S2. Let the obtained mud material stand and age for 4-12 hours; S3. The aged clay is shaped to obtain a shaped body; S4. Dry the obtained molded body to obtain a dried blank; S5. Place the dried blank in a calcining device for calcination. After calcination, cool it to room temperature with the furnace to obtain the calcium-based adsorbent for flue gas desulfurization.
[0014] After adopting the above technical solution, the beneficial effects of the present invention are: The pore-forming agent is a compound of expanded perlite and urea. Expanded perlite is a porous mineral material formed through heating and expansion, with an internal honeycomb-like porous structure. During the adsorbent formation process, it acts as a rigid macroporous framework, pre-constructing and reserving macroporous structures within the adsorbent to provide channels for gas diffusion. Urea releases gas upon thermal decomposition during the calcination stage, forming numerous interconnected mesoporous structures within the adsorbent matrix. The rigid macropores provided by expanded perlite and the interconnected mesopores generated by urea decomposition work synergistically to construct a multi-level pore system with gradient distribution characteristics, facilitating the rapid diffusion of SO2 gas from flue gas into the adsorbent.
[0015] The combination of hydrotalcite and palygorskite can synergistically construct a hierarchical porous structure, increasing the specific surface area and thus improving desulfurization efficiency. Simultaneously, hydrotalcite, upon thermal decomposition, generates Mg-Al composite metal oxides with a high specific surface area. When in contact with water-containing flue gas, it can preferentially adsorb and capture acidic gases such as HCl and HF due to its memory effect, effectively preventing the active sites in calcium-based desulfurizers from being preferentially consumed by these acidic components, ensuring that the calcium-based components are used for the main desulfurization reaction. Detailed Implementation
[0016] The features and exemplary embodiments of various aspects of the present invention will now be described in detail. In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments.
[0017] Step 1: Ingredients and Mixing The calcium hydroxide, composite clay minerals, diatomaceous earth, fly ash, titanium dioxide, zirconium oxide, anhydrous sodium sulfate, catalyst, and expanded perlite, weighed according to the formula, are added to a mixer and dry-mixed at 350 r / min for 15 min to obtain a uniform mixed dry powder. The specifications of each powder are as follows: Calcium hydroxide, using 200-300 mesh fine powder, is used as the main component in the desulfurization reaction; composite clay minerals, composed of 300-400 mesh hydrotalcite and palygorskite in a mass ratio of 1-3:2-4, are used to construct hierarchical channels; diatomaceous earth, using 325-400 mesh fine powder, possesses abundant natural macroporous and mesoporous structures, providing a natural porous carrier; fly ash, using 200-300 mesh fine powder, contains porous microspheres that, in addition to constructing hierarchical channels, can fill the gaps between large particles, reducing the carbon content in the green body. The proportion of harmful macropores; at the same time, the silica-alumina components in fly ash can enhance the structural strength of the adsorbent; the mesh size of titanium dioxide and zirconium oxide is 500-800 mesh; the mesh size of anhydrous sodium sulfate is 200-300 mesh; the catalyst is composed of one or more of ferric sulfate, cerium oxide, magnesium oxide, and manganese sulfate, all of which are 100-300 mesh, to participate in the catalytic reaction, accelerate the adsorption and conversion of SO2, and improve the reaction rate and desulfurization efficiency; expanded perlite uses 50-70 mesh particles to construct the main macroporous channels.
[0018] Weigh out 20% to 35% of the total mass of the mixed dry powder with water, and set aside.
[0019] First, take 50% of the total water volume separately, add surfactant, dispersant, urea and citric acid into it, and stir at 200 r / min until it is evenly dissolved to obtain the base solution.
[0020] The surfactant is one or more of polyethylene glycol, sodium lignosulfonate, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide; the dispersant is one or more of sodium hexametaphosphate, sodium pyrophosphate, and sodium polyacrylate.
[0021] Citric acid can chelate catalyst metal ions in the system, promoting uniform catalyst dispersion. During the calcination and heating process, citric acid gradually decomposes, and metal ions are released in situ and highly dispersed in the adsorbent channels, preventing local enrichment and sintering of catalytic components and obtaining a large number of highly dispersed catalytic active sites.
[0022] While stirring at 200 rpm, slowly add 30# standard silica sol (pH 9-10) dropwise to the remaining water. After the addition is complete, continue stirring to ensure the material is evenly mixed. Maintaining the stirring speed at 200 rpm, add aluminum phosphate powder with a particle size ≤2μm to the system and continue stirring until the aluminum phosphate powder is fully dispersed to obtain a uniform composite sol. Prepare and use immediately.
[0023] Transfer the mixed dry powder to a ply kneading machine, start the stirring, and slowly add the pre-prepared base liquid in a thin stream while stirring. After adding the liquid, continue kneading for 15 minutes to obtain a preliminarily mixed wet clay. After kneading, let it stand for 30 minutes, then add the pre-prepared composite sol and continue kneading for 15 minutes to obtain a clay with uniform color and good plasticity.
[0024] Step Two: Stale The clay is aged for 4 to 12 hours at a temperature of 10℃ to 35℃ and a humidity of 60% to 95% to allow moisture to fully diffuse and penetrate the clay, eliminate local unevenness in moisture content, and reduce the risk of cracking during subsequent molding.
[0025] Step 3: Shaping The aged clay is processed by an extrusion molding machine to obtain a molded body. The preferred size of the molded body is a cylinder with a diameter of 4-8 mm and a length of 5-20 mm, or a sphere with a diameter of 4-8 mm.
[0026] Step 4: Drying To prevent cracking caused by uneven shrinkage during the drying process, this process employs segmented drying. First, the molded body is dried in a ventilated environment at a temperature of 30℃~45℃ for 1.5~2 hours to obtain a first-drying green body; then, the temperature is raised to 50℃~60℃ and dried in a ventilated environment for another 1~2 hours to obtain a second-drying green body; finally, the temperature is raised to 70℃~80℃ and dried in a ventilated environment for 2~3 hours to obtain a third-drying green body.
[0027] Step 5: Calcination The three-stage dried green body is fed into a calcining device for calcination, with the maximum calcination temperature controlled at 320℃ to avoid thermal decomposition of calcium hydroxide.
[0028] The temperature is increased to 120℃ at a rate of 1.5℃~3℃ / min and held for 1~1.5h. This process slowly removes residual adsorbed water and pore-bound water from the billet, avoiding rapid expansion of water vapor within the billet that could cause particle bursting.
[0029] The temperature is increased to 220℃ at a rate of 2–5℃ / min and held for 2–3 hours, maintaining an oxygen content ≥25%. In this oxygen-rich environment, organic additives such as polyethylene glycol and sodium lignosulfonate in the green body begin to oxidize and decompose, while urea vaporizes and escapes, generating micropores in situ within the green body, thus achieving initial pore formation. Silica sol undergoes initial dehydration and condensation, and aluminum phosphate begins to dehydrate its hydroxyl groups, gradually forming a primary adhesive network.
[0030] Second calcination stage After the initial heat treatment at 220℃, the temperature is increased to 320℃ at a rate of 1–3℃ / min and maintained for 2–4 hours. The silica sol and aluminum phosphate composite bonding system undergoes deep dehydration, condensation, and cross-linking reactions, generating a large number of stable Si-O-Si and Si-O-Al covalent bonds. This forms a dense and porous three-dimensional inorganic bonding network at the interface of powder particles such as calcium hydroxide, clay minerals, and fly ash, thoroughly solidifying the overall skeletal structure of the adsorbent and significantly improving the product's compressive strength, wear resistance, and anti-pulverization ability.
[0031] Based on the above process flow, the various exemplary embodiments of the present invention will be described in detail below.
[0032] Example 1 45 parts by weight of calcium hydroxide, 10 parts by weight of composite clay mineral, 3 parts by weight of diatomaceous earth, 4 parts by weight of fly ash, 3 parts by weight of titanium dioxide, 3 parts by weight of zirconium oxide, 2 parts by weight of anhydrous sodium sulfate, 2 parts by weight of cerium oxide, and 3 parts by weight of expanded perlite were added into a mixer. The composite clay mineral was composed of hydrotalcite and palygorskite in a mass ratio of 1:2. The mixture was then dry-mixed at a speed of 350 r / min for 15 min to obtain a uniform mixed dry powder.
[0033] Weigh out 20% of the total mass of the mixed dry powder with water and set aside.
[0034] Take 50% of the total water volume separately, add 1 part polyethylene glycol, 1 part sodium hexametaphosphate, 1 part urea and 1 part citric acid to it, and stir at 200 r / min until it is evenly dissolved to obtain the base solution.
[0035] While stirring at 200 rpm, slowly add 3.5 parts of silica sol dropwise to the remaining water. After the addition is complete, continue stirring to ensure the material is evenly mixed. Maintaining the stirring speed at 200 rpm, add 2.5 parts of aluminum phosphate powder to the system and stir to disperse, obtaining a uniform composite sol.
[0036] Transfer the mixed dry powder to a ply kneading machine, start the mixer, and slowly add the pre-prepared base liquid in a thin stream while maintaining the mixer. After adding the liquid, continue kneading for 15 minutes to obtain a preliminarily mixed wet ply. After kneading, let it stand for 30 minutes, then add the pre-prepared composite sol and continue kneading for 15 minutes to obtain the ply.
[0037] The clay was aged at 35℃ and 80% humidity for 4 hours to allow moisture to fully diffuse and penetrate the clay, eliminating uneven drying and reducing the risk of cracking during subsequent molding. The aged clay was then processed using an extrusion molding machine to obtain cylindrical molded bodies with a diameter of 6mm and a length of 15mm.
[0038] During drying, the molded body is first placed in a ventilated environment at 45°C and dried for 1.5 hours to obtain a first-drying blank; then the temperature is raised to 55°C and dried for another hour in a ventilated environment to obtain a second-drying blank; then the temperature is raised to 80°C and dried for another 2 hours in a ventilated environment to obtain a third-drying blank.
[0039] The three-stage dried green body was fed into a calcining apparatus for calcination: the temperature was increased to 120℃ at 2℃ / min and held for 1 hour; then increased to 220℃ at 5℃ / min and held for 2 hours; after holding at 220℃, the temperature was increased to 320℃ at 2.5℃ / min and held for 2 hours. Finally, the green body was cooled to room temperature in the furnace to obtain adsorbent A1.
[0040] Example 2 50 parts by weight of calcium hydroxide, 12 parts by weight of composite clay mineral, 4 parts by weight of diatomaceous earth, 6 parts by weight of fly ash, 5 parts by weight of titanium dioxide, 6 parts by weight of zirconium oxide, 3.5 parts by weight of anhydrous sodium sulfate, 5 parts by weight of cerium oxide, and 4.5 parts by weight of expanded perlite were added into a mixer. The composite clay mineral was composed of hydrotalcite and palygorskite in a mass ratio of 2:3. The mixture was then dry-mixed at a speed of 350 r / min for 15 min to obtain a uniform mixed dry powder.
[0041] Weigh out 30% of the total mass of the mixed dry powder with water and set aside.
[0042] Take 50% of the total water volume and add 2 parts polyethylene glycol, 1.5 parts sodium hexametaphosphate, 2 parts urea and 2.5 parts citric acid. Stir at 200 r / min until dissolved and homogeneous to obtain the base solution.
[0043] While stirring at 200 rpm, slowly add 4 parts of silica sol dropwise to the remaining water. After the addition is complete, continue stirring to ensure the material is evenly mixed. Maintaining the stirring speed at 200 rpm, add 3 parts of aluminum phosphate powder to the system and stir to disperse, obtaining a uniform composite sol.
[0044] Transfer the mixed dry powder to a ply kneading machine, start the mixer, and slowly add the pre-prepared base liquid in a thin stream while maintaining the mixer. After adding the liquid, continue kneading for 15 minutes to obtain a preliminarily mixed wet ply. After kneading, let it stand for 30 minutes, then add the pre-prepared composite sol and continue kneading for 15 minutes to obtain the ply.
[0045] The clay was aged at 35℃ and 80% humidity for 4 hours to allow moisture to fully diffuse and penetrate the clay, eliminating uneven drying and reducing the risk of cracking during subsequent molding. The aged clay was then processed using an extrusion molding machine to obtain cylindrical molded bodies with a diameter of 6mm and a length of 15mm.
[0046] During drying, the molded body is first placed in a ventilated environment at 45°C and dried for 1.5 hours to obtain a first-drying blank; then the temperature is raised to 55°C and dried for another hour in a ventilated environment to obtain a second-drying blank; then the temperature is raised to 80°C and dried for another 2 hours in a ventilated environment to obtain a third-drying blank.
[0047] The three-stage dried green body was fed into a calcining apparatus for calcination: the temperature was increased to 120℃ at 2℃ / min and held for 1 hour; then increased to 220℃ at 5℃ / min and held for 2 hours; after holding at 220℃, the temperature was increased to 320℃ at 2.5℃ / min and held for 2 hours. Finally, the green body was cooled to room temperature in the furnace to obtain adsorbent A2.
[0048] Example 3 55 parts by weight of calcium hydroxide, 15 parts by weight of composite clay mineral, 6 parts by weight of diatomaceous earth, 10 parts by weight of fly ash, 10 parts by weight of titanium dioxide, 8 parts by weight of zirconium oxide, 5 parts by weight of anhydrous sodium sulfate, 6 parts by weight of cerium oxide, and 5 parts by weight of expanded perlite were added into a mixer. The composite clay mineral was composed of hydrotalcite and palygorskite in a mass ratio of 3:4. The mixture was then dry-mixed at a speed of 350 r / min for 15 min to obtain a uniform mixed dry powder.
[0049] Weigh out 35% of the total mass of the mixed dry powder with water and set aside.
[0050] Take 50% of the total water volume separately, add 3 parts polyethylene glycol, 2 parts sodium hexametaphosphate, 3 parts urea and 3 parts citric acid, and stir at 200 r / min until dissolved evenly to obtain the base solution.
[0051] While stirring at 200 rpm, slowly add 4.5 parts of silica sol dropwise to the remaining water. After the addition is complete, continue stirring to ensure the material is evenly mixed. Maintaining the stirring speed at 200 rpm, add 3.5 parts of aluminum phosphate powder to the system and stir to disperse, obtaining a uniform composite sol.
[0052] Transfer the mixed dry powder to a ply kneading machine, start the mixer, and slowly add the pre-prepared base liquid in a thin stream while maintaining the mixer. After adding the liquid, continue kneading for 15 minutes to obtain a preliminarily mixed wet ply. After kneading, let it stand for 30 minutes, then add the pre-prepared composite sol and continue kneading for 15 minutes to obtain the ply.
[0053] The clay was aged at 35℃ and 80% humidity for 4 hours to allow moisture to fully diffuse and penetrate the clay, eliminating uneven drying and reducing the risk of cracking during subsequent molding. The aged clay was then processed using an extrusion molding machine to obtain cylindrical molded bodies with a diameter of 6mm and a length of 15mm.
[0054] During drying, the molded body is first placed in a ventilated environment at 45°C and dried for 1.5 hours to obtain a first-drying blank; then the temperature is raised to 55°C and dried for another hour in a ventilated environment to obtain a second-drying blank; then the temperature is raised to 80°C and dried for another 2 hours in a ventilated environment to obtain a third-drying blank.
[0055] The three-stage dried green body was fed into a calcining apparatus for calcination: the temperature was increased to 120℃ at 2℃ / min and held for 1 hour; then increased to 220℃ at 5℃ / min and held for 2 hours; after holding at 220℃, the temperature was increased to 320℃ at 2.5℃ / min and held for 2 hours. Finally, the furnace was cooled to room temperature to obtain adsorbent A3.
[0056] Comparative Example 1 The addition of composite clay minerals was omitted, while the remaining raw material ratios, preparation process parameters, and operating steps were the same as in Example 2, resulting in adsorbent D1.
[0057] Comparative Example 2 The composite clay minerals in the formula were replaced with an equal amount of palygorskite powder, and the use of hydrotalcite was eliminated. The remaining raw material ratios, preparation process parameters and operation steps were the same as in Example 2, and adsorbent D2 was obtained.
[0058] Comparative Example 3 The addition of titanium dioxide was omitted, while the remaining raw material ratios, preparation process parameters, and operating steps were the same as in Example 2, resulting in adsorbent D3.
[0059] Comparative Example 4 The addition of zirconium oxide was omitted, while the remaining raw material ratios, preparation process parameters, and operating steps were the same as in Example 2, to obtain adsorbent D4.
[0060] Comparative Example 5 The addition of anhydrous sodium sulfate was omitted, while the remaining raw material ratios, preparation process parameters, and operating steps were consistent with those in Example 2, resulting in the preparation of adsorbent D5.
[0061] The desulfurization performance of the adsorbents prepared in Examples 1-3 and Comparative Examples 1-5 was tested. Each adsorbent was filled into a corresponding quartz reaction tube with an inner diameter of 20 mm, and simulated flue gas was introduced. The SO2 concentration at the reactor outlet was continuously monitored, and the test results are shown in Table 1.
[0062] Simulated flue gas composition (volume fraction): 0.2% SO2, 6% O2, 8% H2O, balance N2. Tested at atmospheric pressure, reaction temperature controlled at 140℃, flue gas volume hourly space velocity (VHSV) 1000 h⁻¹. -1 .
[0063] Table 1 Performance Test Results
[0064] Compared to Example 2, Comparative Example 1, without the addition of composite clay minerals, failed to construct a multi-level pore structure of hydrotalcite-palmitite composite, resulting in a significant decrease in the BET specific surface area. This is because the lack of a multi-level pore structure makes it difficult for flue gas to diffuse into the adsorbent, preventing a large number of internal calcium-based active sites from participating in the reaction. This demonstrates that composite clay minerals are a key component for constructing a high specific surface area multi-level pore structure and ensuring long-term stable desulfurization.
[0065] Comparative Example 2 replaced the composite clay minerals with an equal amount of palygorskite, eliminating the addition of hydrotalcite. Palygorskite provides one-dimensional mesopores, retaining a certain pore structure, and its specific surface area is better than that of Comparative Example 1, but significantly lower than that of Example 2. Hydrotalcite, upon thermal decomposition, generates Mg-Al composite metal oxides with high specific surface area. These oxides, in synergy with palygorskite, expanded perlite, and other components, can construct a hierarchical porous structure, confirming the synergistic effect of hydrotalcite and palygorskite in constructing hierarchical pores, increasing specific surface area, and extending effective desulfurization time. In practical applications, when hydrotalcite comes into contact with water-containing flue gas, it can preferentially adsorb and capture acidic gases such as HCl and HF due to its memory effect, thereby effectively preventing the active sites in the calcium-based desulfurizer from being preferentially consumed by the aforementioned acidic components, ensuring that the calcium-based components are used for the main desulfurization reaction.
[0066] Titanium dioxide exhibits catalytic oxidation activity. Anatase titanium dioxide lattices contain numerous defects and dislocations, generating more oxygen vacancies to capture electrons; these surface oxygen vacancies can serve as active centers for SO2 oxidation. Zirconia enhances the catalyst's thermal stability and possesses both Lewis and Brønsted acidic sites on its surface, allowing SO2 to be adsorbed and participate in the reaction. Comparative Examples 3 and 4 lack the aforementioned components, resulting in lower desulfurization efficiencies compared to Example 2.
[0067] The specific surface area of Comparative Example 5 changed very little compared to Example 2, indicating that anhydrous sodium sulfate essentially does not alter the pore structure and specific surface area. Under conditions of water content in the flue gas, a small amount of anhydrous sodium sulfate dissolves slightly on the pore surface, adjusting the surface polarity of the pore walls, stabilizing the nano-thin water film on the calcium hydroxide surface, and dissociating to generate Na. + It can achieve ion modification of the pore interface, improve the ion migration rate in the thin liquid film, promote the solid-gas reaction of calcium hydroxide and SO2, and improve the utilization rate of calcium-based active components.
[0068] According to the embodiments of the present invention described above, these embodiments do not exhaustively describe all the details, nor do they limit the invention to specific embodiments.
Claims
1. A calcium-based adsorbent for flue gas desulfurization, characterized in that, The components include the following parts by weight: Calcium hydroxide 45-55 parts, composite clay mineral 10-15 parts, binder 6-8 parts, auxiliary agent 6-10 parts, titanium dioxide 3-10 parts, zirconium oxide 3-8 parts, diatomaceous earth 3-6 parts, fly ash 4-10 parts, anhydrous sodium sulfate 2-5 parts, catalyst 2-6 parts, citric acid 1-3 parts. The composite clay mineral is composed of hydrotalcite and palygorskite in a mass ratio of 1-3:2-4.
2. The calcium-based adsorbent for flue gas desulfurization according to claim 1, characterized in that: The adhesive consists of 3.5 to 4.5 parts silica sol and 2.5 to 3.5 parts aluminum phosphate.
3. The calcium-based adsorbent for flue gas desulfurization according to claim 1, characterized in that: The catalyst is one or more of ferric sulfate, cerium oxide, magnesium oxide, and manganese sulfate.
4. The calcium-based adsorbent for flue gas desulfurization according to claim 1, characterized in that: The auxiliary agent consists of 1 to 3 parts surfactant, 3 to 5 parts pore-forming agent and 1 to 2 parts dispersant.
5. The calcium-based adsorbent for flue gas desulfurization according to claim 4, characterized in that: The pore-forming agent is a compound of expanded perlite and urea in a mass ratio of 3-5:1-3.
6. The calcium-based adsorbent for flue gas desulfurization according to claim 4, characterized in that: The surfactant is one or more of polyethylene glycol, sodium lignosulfonate, sodium dodecyl sulfate, and hexadecyltrimethylammonium bromide.
7. The calcium-based adsorbent for flue gas desulfurization according to claim 4, characterized in that: The dispersant is one or more of sodium hexametaphosphate, sodium pyrophosphate, and sodium polyacrylate.
8. A method for preparing a calcium-based adsorbent for flue gas desulfurization as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Weigh each raw material according to the formula proportions, add 20-35% water of the total mass of the raw materials, stir and mix evenly to obtain mud; S2. Let the obtained mud material stand and age for 4-12 hours; S3. The aged clay is shaped to obtain a shaped body; S4. Dry the obtained molded body to obtain a dried blank; S5. Place the dried blank in a calcining device for calcination. After calcination, cool it to room temperature with the furnace to obtain the calcium-based adsorbent for flue gas desulfurization.